05 - PROPOSAL FOR A GENERAL INDEX OF QUALITY OF LIFE FROM THE INSTRUMENT WHOQOL-BRIEF IN ACADEMIC ENGINEERING OF UTFPR (Fiep Bulletin - online, 2011)
The Federal Technological University of Paraná State - UTFPR included in engineering courses in the humanities discipline Quality of Life to make their scholarly importance of healthy habits for the quality of life. This study seeks to these scholars propose a general index of quality of life (IGQV), than building a spreadsheet for calculation of scores and a table of percentiles for the analysis and comparison of data. The majority (89%) of students are males with a mean age of 19.7 years. Data were collected by the WHOQOL-BRIEF questionnaire to be fully answered. The analysis of correlation showed high correlation between the rate of GIQV and the four areas of the instrument (physical, psychological, social relationships and environment). With the results obtained and analyzed it appears that the GIQV can be used to represent the state of quality of life of the academic engineering courses of UTFPR.
Keywords: quality of life; academic of engineering; health; lifestyle